Cerebellar metastasis from serous adenocarcinoma of the ovary mimicking pilocytic astrocytoma - Tandon, Vivek; Garg, Kanwaljeet; Mahapatra, A (Asian Journal of Neurosurgery, 2012)
Serous adenocarcinoma of the ovary rarely can present with solitary solid -cystic cerebellar metastasis, mimicking pilocytic astrocytoma. A middle aged women, who underwent total abdominal hysterectomy with bilateral salpingoopherectomy and adjuvant chemotherapy for ovarian adenocarcinoma, presented to us with the history of headache, vomiting, and imbalance. Contrast enhanced magnetic resonance imaging (MRI) showed solitary cerebellar, solid cystic lesion with cyst lining and solid portion enhancing on contrast which was mimicking pilocytic astrocytoma and there was no perilesional edema. Gross total excision of the cerebellar lesion was done followed by resolution of her symptoms. Histopathology showed metastatic adenocarcinoma consistent with the primary ovarian carcinoma. In patients of ovarian carcinoma, presenting with features of raised intracranial pressureICP] thorough investigations must be done to rule out metastasis. Solitary metastasis of the cerebellum because of ovarian carcinoma may mimic pilocytic astrocytoma.
Keywords: Cerebellar metastases; ovarian cystadenocarcinoma; pilocytic astrocytoma